Newly discovered clouting interplay between matrix metalloproteinases structures and novel quaternary Ammonium K21: computational and in-vivo testing - Ranjeet Ajit Bapat; Kit-Kay Mak; Mallikarjuna Rao Pichika; Jia Chern Pang; Seow Liang Lin; Suan Phaik Khoo; Umer Daood (BMC, 2024)
Abstract Aims and objectives To analyze anti-MMP mode of action of Quaternary Ammonium Silane (QAS, codenamed as k21) by binding onto specific MMP site using computational molecular simulation and Anti-Sortase A (SrtA) mode of action by binding onto specific site using computational molecular simulation. Materials and methods In silico Molecular Dynamics (MD) was used to determine the interactions of K21 inside the pocket of the targeted protein (crystal structure of fibroblast collagenase-1 complexed to a diphenyl-ether sulphone based hydroxamic acid; PDB ID: 966C; Crystal structure of MMP-2 active site mutant in complex with APP-derived decapeptide inhibitor. MD simulations were accomplished with the Desmond package in Schrödinger Drug Discovery Suite. Blood samples (~ 0.5 mL) collected into K2EDTA were immediately transferred for further processing using the Litron MicroFlow® PLUS micronucleus analysis kit for mouse blood according to the manufacturer's instructions. Bacterial Reverse Mutation Test of K21 Molecule was performed to evaluate K21 and any possible metabolites for their potential to induce point mutations in amino acid-requiring strains of Escherichia coli (E. coli) (WP2 uvrA (tryptophan-deficient)). Results Molecular Simulation depicted that K21 has a specific pocket binding on various MMPs and SrtA surfaces producing a classical clouting effect. K21 did not induce micronuclei, which are the result of chromosomal damage or damage to the mitotic apparatus, in the peripheral blood reticulocytes of male and female CD-1 mice when administered by oral gavage up to the maximum recommended dose of 2000 mg/kg. The test item, K21, was not mutagenic to Salmonella typhimurium (S. typhimurium) strains TA98, TA100, TA1535 and TA1537 and E. coli strain WP2 uvrA in the absence and presence of metabolic activation when tested up to the limit of cytotoxicity or solubility under the conditions of the test. Conclusion K21 could serve as a potent protease inhibitor maintaining the physical and biochemical properties of dental structures.